2001
DOI: 10.1097/00001756-200110080-00013
|View full text |Cite
|
Sign up to set email alerts
|

Human brain mapping of auditory imagery: event-related functional MRI study

Abstract: We used event-related fMRI methodology to investigate human brain activity during auditory imagery. A series of susceptibility-weighted MR images covering the whole brain were acquired to obtain blood oxygenation level-dependent (BOLD) signal changes associated with the imagery event of hearing simple monotone. Group analysis across the 12 right-handed subjects revealed activations in the medial and inferior frontal gyri, precuneus, middle frontal gyri, superior temporal gyri, and anterior cingulate gyri. Bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
54
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(68 citation statements)
references
References 24 publications
13
54
0
1
Order By: Relevance
“…3). This result is in line with several observations on sound and music imagery, which found activity only in the secondary auditory cortex but not in A1 (Ducreux et al, 2003;Halpern and Zatorre, 1999;Kraemer et al, 2005;Yoo et al, 2001;Zatorre and Halpern, 2005). It is interesting in this regard that our subjects rated the vividness of imagined singing as high and reported no problems in attention during the imagery task.…”
Section: Areas Involved In Auditory Controlsupporting
confidence: 93%
See 1 more Smart Citation
“…3). This result is in line with several observations on sound and music imagery, which found activity only in the secondary auditory cortex but not in A1 (Ducreux et al, 2003;Halpern and Zatorre, 1999;Kraemer et al, 2005;Yoo et al, 2001;Zatorre and Halpern, 2005). It is interesting in this regard that our subjects rated the vividness of imagined singing as high and reported no problems in attention during the imagery task.…”
Section: Areas Involved In Auditory Controlsupporting
confidence: 93%
“…Primary auditory cortex activation in the absence of auditory input has been found for short gaps of silence (lasting 2-5 s) that were inserted at different points during the soundtrack of familiar music (Kraemer et al, 2005) and in a sound detection task during the preceding silence of the emerging sounds (Voisin et al, 2006). A further report of primary auditory activation during mental imagery of a computer generated monotone (C maj ) comes from Yoo and colleagues (Yoo et al, 2001) but a recent inspection of the exact locus of activation indicated in that study questioned their results (Halpern et al, 2004). More compelling evidence exists regarding the contribution of secondary (or association) auditory cortex during mental imagery of complex, meaningful sounds (Bunzeck et al, 2005;Halpern and Zatorre, 1999;Halpern et al, 2004;Shergill et al, 2000;Shergill et al, 2001;Zatorre et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Precuneus activation has also been reported for auditory imagery (Yoo et al, 2001) and for the recognition of familiar sounds (Maeder et al, 2001) and voices (Nakamura et al, 2001)-as well as for recognition memory in general (Henson et al, 2000;Herath et al, 2001). Precuneal activity in the present study, thus, might alternatively be taken to suggest that earlier learned words elicit a greater recognition response in the brain.…”
Section: Discussionsupporting
confidence: 67%
“…Imagination seems to activate the same brain structures within the same modality as actual perception (Kosslyn et al, 2001). In fact, imagery of various sensory stimulations and ocular motor performances activate areas that overlap with those activated under "real" conditions such as acoustic (Yoo et al, 2001;Halpern and Zatorre, 1999), visual (Mellet et al, 1998;Wexler et al, 1998), and ocular motor areas (Bodis-Wollner et al, 1997;Law et al, 1997). Our study strikingly showed that several sensory modalities were activated simultaneously in single subject and group analyses.…”
Section: An "Interoceptive Mental State" (Eyes Closed ͼ Eyes Open)?supporting
confidence: 48%